Ascertaining Women's God-Ordained Roles: An Interpretation of 1 Timothy 2:15 - Köstenberger, Andreas J. (Bulletin for biblical research, 1997)
Puzzling as it is, the statement of 1 Tim 2:15, "Women will be saved through childbearing," is a significant passage regarding the issue of women's God-ordained roles. After an initial survey of the passage's history of interpretation, the essay is devoted to a detailed investigation of the phrase σωθήσεται διὰ τῆς τεκνογονίας. Subsequently, the present passage is interpreted in light of a major but thus far overlooked theme found in 1 Timothy. The article concludes with a brief discussion of some implications for the contemporary church and culture.